From monarchy to the republic: European Union democracy promotion in Nepal - Robot Limbu (2021)
The study evaluated the role played by the European Union in facilitating the swift transition of Nepal from a monarchy to a democratic republic where the people exercised control over the leadership and governance of the country through their elected representatives. Nepal had been trying to shift from centralized absolute power of a kingdom to the decentralized distributive power of the people through a democracy for quite some time, but failed in most attempts, as the leadership of the kingdom would not allow for the integration of democratic ideologies in the governance of the country. The study used qualitative secondary reviews, with a particular focus on case studies, to identify and establish the significance of the EU’s involvement in facilitating the democratization of Nepal. The results obtained from this study indicated that the European Union was actively involved in the process of democratization of Nepal, whereby it provided humanitarian assistance, and financial aid, in addition to interfering as a member of the international community in calling out the injustices of the government, especially human rights injustices. The results established that the EU formally began supporting the democratization process in the country in the year 2006, during the II People’s Movement, which resulted in a successful regime change in Nepal, and a transition in the style of governance, with preference for a democracy over a monarchy, as this was the best political solution of protecting human rights in Nepal, while promoting economic growth and development.